2011
DOI: 10.1038/emboj.2011.328
|View full text |Cite
|
Sign up to set email alerts
|

Dual role of FoxA1 in androgen receptor binding to chromatin, androgen signalling and prostate cancer

Abstract: High androgen receptor (AR) level in primary tumour predicts increased prostate cancer‐specific mortality. However, the mechanisms that regulate AR function in prostate cancer are poorly known. We report here a new paradigm for the forkhead protein FoxA1 action in androgen signalling. Besides pioneering the AR pathway, FoxA1 depletion elicited extensive redistribution of AR‐binding sites (ARBs) on LNCaP‐1F5 cell chromatin that was commensurate with changes in androgen‐dependent gene expression signature. We id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
388
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 340 publications
(419 citation statements)
references
References 64 publications
26
388
5
Order By: Relevance
“…This resembles our observations for GATA3 and its ability to both positively and negatively impact ESR1 recruitment in breast cancer cells. A distinct difference is that in breast cancer cells lacking GATA3, we observed substantial epigenetic changes at distal enhancers, whereas in the prostate cells, enhancer accessibility was not affected when FOXA1 was silenced (Sahu et al 2011;Wang et al 2011). In general, forkhead and GATA members appear to facilitate nuclear receptor access to their DNA response elements.…”
Section: Discussionmentioning
confidence: 64%
“…This resembles our observations for GATA3 and its ability to both positively and negatively impact ESR1 recruitment in breast cancer cells. A distinct difference is that in breast cancer cells lacking GATA3, we observed substantial epigenetic changes at distal enhancers, whereas in the prostate cells, enhancer accessibility was not affected when FOXA1 was silenced (Sahu et al 2011;Wang et al 2011). In general, forkhead and GATA members appear to facilitate nuclear receptor access to their DNA response elements.…”
Section: Discussionmentioning
confidence: 64%
“…More recent genome-wide profiling of transcription factor binding combined with loss-of-function analyses has revealed that some transcription factors act as pioneer factors for others (53,54). Thus, Forkhead box A1 (FoxA1) has been shown to function as a pioneer factor for the estrogen receptor (53,55,56) and the androgen receptor (55,(57)(58)(59), PU.1 has been shown to facilitate C/EBP␤ and LXR binding during macrophage development (40), and C/EBPs and AP-1 have been shown to facilitate glucocorticoid receptor (GR) binding in several different model systems (60)(61)(62)(63). The current study extends cooperative binding of transcription factors to the major regulators of adipocyte differentiation and demonstrates that they can act as mutual pioneer factors for each other.…”
Section: Discussionmentioning
confidence: 99%
“…In ER + breast cancer cells, ER binding requires FOXA1 at many binding sites showing the role of FOXA1 in driving hormone response of these tumors (90). Similarly, AR binding is also influenced by FOXA1; indeed some AR binding sites are lost in cells depleted of FOXA1; however many sites are also gained suggesting a more complex relationship of FOXA1 with AR than with ER (87,91). Also, FOXM1 is amplified in some breast cancers (92), in non-Hodgkin's lymphomas (93) or in malignant peripheral nerve sheath tumors (94).…”
Section: Pioneer Factors In Cancermentioning
confidence: 99%
“…And indeed, FOX family genes are involved in several cancers (reviewed in (86). Overexpression of Foxa1 is associated with a poor prognosis in prostate cancer (87) while it is generally a good prognosis of breast cancer (88). Point mutations of FOXA1 were also found in some prostate cancers and this was associated with decreased androgen signaling and increased tumor growth (89).…”
Section: Pioneer Factors In Cancermentioning
confidence: 99%